Pengaruh Kecerdasan Emosional dan Stres Kerja terhadap Kinerja Karyawan wift Indonesia di CV. Wijaya Family Tasikmalaya - Kharisma Nur (PT Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of emotional intelligence on employee performance at WIFT INDONESIA (CV. WIJAYA FAMILY TASIKMALAYA), to determine the effect of work stress on employee performance at WIFT INDONESIA (CV. WIJAYA FAMILY TASIKMALAYA) and to determine the effect of emotional intelligence and work stress on the performance of WIFT INDONESIA employees (CV. WIJAYA FAMILY TASIKMALAYA). The sample in this study were WIF INDONESIA employees (CV. WIJAYA FAMILY TASIKMALAYA), totaling 83 people. This research was conducted by collecting data with a questionnaire data collection technique, then testing the data with multiple linear regression analysis. The results showed that emotional intelligence has a significant effect on employee performance at WIF INDONESIA (CV. WIJAYA FAMILY TASIKMALAYA). Significant effect of work stress on employee performance at WIF INDONESIA (CV. WIJAYA FAMILY TASIKMALAYA). Significant effect of emotional intelligence and work stress on employee performance at WIF INDONESIA (CV. WIJAYA FAMILY TASIKMALAYA)